Discurso, sujeito e corpo: a grafia da dor como ins(es)crituração de si - Jordão, Aline Bedin (2020)
The present thesis addresses the order of the body as a discursive materiality that enables the inscription/ ―escrituração‖ /writting of subject. The corpography of pain in the process of becoming a woman is discussed through the body, more specifically in situations where the subject produces cuts/self-mutilations. This work is affiliated with the theoretical-analytical field of French Discourse Analysis, recommended by Pêcheux, in France, and unfolded by Eni Orlandi in Brazil, in dialogue with Psychoanalysis assumptions. The thesis situates the subject endowed with unconscious and ideologically challenged, who experiences a process of imaginary construction of the body, which composes looks and speeches about it. A cuted and mutilated body, whose entrails, grooves and bleeds produce a corpography, a writing, a gesture of ―re(ex)sistência‖. In this study, three discursive materialities are analyzed - posts made by girls who cut themselves on Facebook, blogs and Tumblr - images and narratives that were published on the web; discursive sequences of the Black Swan film (following the path of Nina, the queen of the Swans, and the antagonism of the subject positions demanded by her mother and her trainer from the ballet company); clippings from the fiction ―UmaDuas”, by Eliane Brum, written in blood, witnessing Laura's pain in her process of separating from her mother and positioning herself as a woman. When working with archives of audiovisual status - images, photography, film materiality - with fictional writing and digital speech, considered as discursive processes, constitutively incomplete and contradictory, tracing a path for reading the archive that takes into account the productions and reproductions of speeches: marks of polysemy, opacities, places of plurivocity of the senses. The analysis of the significant material imbrications of these archives has led to attention the elements of discursive memory, ideological components and contradictions between the subject positions in such materials. As regularities, it's seen that the body announces and denounces a corpography of subjective pain, in addition to putting into play the discursive and ideological formations of social practices. Still, the paradox between what lies in the field of excesses, overflows, the imperative of jouissance, completeness, ideals, and what lies in the field of emptiness, lack, helplessness, pain, fragility of symbolic references, the erasure of alterity and the destitution/disappearance of the subject of desire, elements linked to the conditions of production linked to the contemporary subject-historical form. In addition, the body is situated as a living archive, which produces a mosaic of lines, cuts, marks, scars that discursivize the problem of the constitution of femininity. The outline of the writing, the blade or the tears in the skin tell a story, contain memories, appeal for inscription. They stage something of mourning, loss, enjoyment, the real. They beg for borders and frontiers, for looks and eavesdropping. They are configured as sayings on the scene: in the body, in the blade edge, in digital space, in the writing that makes a body of letters. Still, they refer to what has been denied the social symptom and which returns, in a sinister, strangely familiar way, through the body and its insides, its holes, its cuts. Return of what does not cease to enroll. Sayings from a writing that re-calls for inscription.